Respuesta :

Answer:

d:) 1024

Step-by-step explanation:

Evaluate (4 x^3)^2 where x = 2:

(4 x^3)^2 = (4×2^3)^2

Multiply each exponent in 4×2^3 by 2:

4^2 (2^3)^2

Multiply exponents. (2^3)^2 = 2^(3×2):

2^(3×2)×4^2

4^2 = 16:

2^(3×2)×16

3×2 = 6:

2^6×16

2^6 = (2^3)^2 = (2×2^2)^2:

(2×2^2)^2 16

2^2 = 4:

(2×4)^2 16

2×4 = 8:

8^2×16

8^2 = 64:

64×16

| | 6 | 4

× | | 1 | 6

| 3 | 8 | 4

| 6 | 4 | 0

1 | 0 | 2 | 4:

Answer:  1024

Your answer is D Bc first you solve the explanation step by step,multiply the exponents ,multiply again ,and that’s how you solve this problem